Inflammatory, fibrotic and endothelial biomarker profiles in COVID-19 patients during and following hospitalization - Fares Darawshy; Dan Padawer; Abed Qadan; Yaser Salaymeh; Neville Berkman (Scientific Reports)
Abstract Survivors of severe COVID-19 often suffer from long-term respiratory issues, but the molecular drivers of this damage remain unclear. This study explored the dynamics of inflammatory, fibrotic, and endothelial biomarkers in hospitalized COVID-19 patients. Plasma levels of MMP2, MMP7, MMP9, KL-6, IL-6, TNF-α, angiopoietin-2, thrombomodulin, and hyaluronan were measured in 73 hospitalized COVID-19 patients during admission and, in a subset, at follow-up. Pulmonary function tests were performed at follow-up. The majority of patients (82.2%) had severe COVID-19; 14 (19.2%) died within 90 days. During acute illness, IL-6, angiopoietin-2, and hyaluronan levels were significantly elevated compared to healthy controls. Follow-up data from 18 patients showed persistent symptoms such as dyspnea and fatigue. MMP2 and MMP7 levels increased at follow-up, while hyaluronan decreased. Angiopoietin-2 remained elevated and was negatively correlated with forced vital capacity (r = − 0.76, p < 0.01). A machine learning approach revealed that an increase in angiopoietin-2 was the most important biomarker associated with FVC variability. Circulating factors associated with fibrosis and endothelial injury remain elevated in COVID-19 survivors and are associated with impaired lung function, indicating that fibrotic and endothelial damage may underlie post-COVID pulmonary sequelae.